Optimal control for forest management and conservation analysis in dehesa ecosystems - Cerdá, Emilio; Martı´n-Barroso, David (European Journal of Operational Research, 2012)
This paper presents a deterministic ﬁnite time horizon dynamic optimization model aimed to determine optimal paths for artiﬁcial plantations and natural regeneration of two main tree species in dehesa multiple use ecosystems, holm oak (Quercus ilex L.) and cork oak (Q. suber L.). Whilst dehesa forest sustainability problems associated to exhaustive use of grazing resources have been indirectly approached by European Union authorities, providing support for artiﬁcial plantations over treeless land, no mention is made to natural regeneration techniques. In this sense, the formulated model allows for natural regeneration of already established ageing stands as a complement or even a substitute of actual reforestation practices. The proposed methodology is neither designed to determine optimal rotation of tree species nor optimal decorticating or pruning cycles of cork oaks and holm oaks, respectively. Instead, this information enters the model exogenously through knowledge of region speciﬁc silvicultural cycles for those commercially relevant tree species, and the optimisation program acts as an optimal land use allocator and thus a practical tool for policy analysis purposes. In addition to existing cost beneﬁt analysis applications in dehesa ecosystems, the presented model allows in one side eﬃcient evaluation of long term management dynamics —thus oak woodlands sustainability can be tested for suﬃciently large time horizons—, and in the other, management decisions, instead of being forced through predeﬁned scenarios, correspond to the optimal actions a decision agent would take from the complete set of feasible possibilities given actual land use and tree age distributions.
Keywords: artificial plantation (voyant); cork oak woodlands; Forest management; holm oak woodlands; land use; natural regeneration

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
The following values have no corresponding Zotero field: periodical: Handbook Of Operations Research In Natural Resources electronic-resource-num: 10.1007/978-0-387-71815-6
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model